Why do consumers engage in online brand communities – and why should brands care?. Issue 4 (9th April 2021) - van Heerden, Danita; Wiese, Melanie
Abstract : Purpose: The purpose of this paper is to explore consumers' motivations for engaging in Facebook brand communities, and what outcomes brands can gain from online engagement. Design/methodology/approach: An online consumer panel was used to collect data through convenience sampling; 497 useable questionnaires were collected. Findings: The results of the structural equation modelling show that hedonic motivations are more prevalent in Facebook brand communities than utilitarian motivations. When considering the outcomes of online engagement, loyalty towards the brand community is the strongest outcome, followed by word-of-mouth and purchase intention. Research limitations/implications: This research indicates that marketers should focus on creating content on Facebook brand communities that appeals to the hedonic needs of consumers, such as brand likeability, entertainment and interpersonal utility. This type of content will motivate members of these brand communities to engage online. When consumers engage online, it creates benefits for the brand such as loyalty, word-of-mouth and purchase intention. Originality/value: This study presents a framework for investigating consumers' motivation to engage online, based on a theoretical underpinning of both sense of community theory and uses and gratification theory. It also identifies three outcomes for brands that explain why it is worthwhile for firms to invest in engaging with consumers in Facebook brand communities while including a wide range of brand communities.